The Prisoner and the Penguin - Giles Lury (LID Publishing)
" The power of a good story has long been recognised. It seems that, as a race, we humans love a good story. But stories arent just for pure enjoyment - they have long been a powerful tool for teaching. This book is an alternative to the traditional marketing handbook. Rather than a textbook, it is an enjoyable story-book that brings to life some of the key principles of marketing in an easy-to-read, accessible form. Some of these stories are quite remarkable and almost unbelievable; but all are true and remind marketers and businesspeople that the best marketing is something which people tell others about and retell over many years."